Indoor Air Quality Risks in U.S. E-Commerce Fulfillment Centers: A Systematic Review and Modeling-Based Risk Assessment of VOC Exposure - Mosharef Hossain (Information Technology and Science (ITScience), 2025)
E-commerce growth has expanded large, enclosed fulfillment centers employing >1.7 M U.S. workers. VOCs from adhesives, packaging foams, solvents, and diesel equipment pose under-recognized IAQ hazards. PRISMA-guided review (2015–2025) identified 47 studies + 9 reports. A single-zone mass-balance model simulated VOCs at 0.3–3.0 ACH. Risks used EPA inhalation methodology: exposure concentration (EC), Hazard Quotient (HQ), and cancer risk (CR). Formaldehyde commonly ranged 15–120 µg/m³; benzene 2–35 µg/m³. Under 0.3 ACH, modeled steady-state concentration ????88 reached 112 µg/m³ (formaldehyde) and 25 µg/m³ (benzene).s EC-based estimates yielded HQ > 1 for formaldehyde and CR = 1.3×10?? for benzene—exceeding EPA’s acceptable range—despite OSHA compliance. Aggregate HQs > 2.0 indicate additive effects; 1.0 ACH reduced ECs by 40–60%. Fulfillment center workers face material VOC risks invisible to OSHA PEL compliance. Ventilation to ASHRAE 62.1 intake targets (with ?3 ACH in high-emission zones), low-emission materials, continuous IAQ monitoring, and updated standards are urgently needed.